Resveratrol and STAT inhibitor enhance autophagy in ovarian cancer cells - Zhong, L-X (Cell Death Discov, 2016)
Autophagic activity reflects cellular response to drug treatment and can be regulated by STAT3 signaling. Resveratrol inhibits STAT3 activation and causes remarkable growth arrest and cell death of ovarian cancer (OC) cells. However, the autophagic status and its relevance with resveratrol’s anti-OC effects remain unclear. We analyzed the states of autophagic activities, the nature of autophagosomes and the levels of autophagy-related proteins (LC-3, Beclin 1 and STAT3) in resveratrol-treated CAOV-3 and OVCAR-3 OC cells using multiple approaches. We elucidated the correlation of STAT3 inhibition with autophagic activity by treating OC cells with an upstream inhibitor of STAT proteins, AG490. Resveratrol efficiently suppressed growth, induced apoptosis and inactivated STAT3 signaling of the two OC cell lines. We found enhanced autophagic activity accompanied with Beclin-1 upregulation and LC3 enzymatic cleavage in resveratrol-treated OC cells. Immunofluorescent (IF) microscopic and IF-based confocal examinations demonstrated the accumulation of cytoplasmic granules co-labeled with LC3 and cytochrome C in resveratrol- or AG490-treated OC cells. Using electron microscopy, we confirmed an increase in autophagosomes and mitochondrial spheroids in either resveratrol- or AG490-treated OC cells. This study demonstrates the abilities of resveratrol to enhance apoptotic and autophagic activities in OC cells, presumably via inactivating STAT3 signaling. Resveratrol or the selective JAK2 inhibitor also leads to mitochondrial turnover, which would be unfavorable for OC cell survival and sensitize OC cells to resveratrol.